Leading article: how can I optimise my role as a leader within the surgical team?. Issue 8 (October 2016) - Green, B.; Mitchell, D.A.; Stevenson, P.; Kane, T.; Reynard, J.; Brennan, P.A.
Abstract: Leadership is uncommonly taught formally at any level in surgical training, and is not often evaluated formally either within assessment programmes or during appraisal. Good leadership skills in oral and maxillofacial surgery (OMFS) include professionalism, technical competence, motivation, innovation, ability to communicate, resilience, and effective teaching. They also include the recognition of when and how to "follow" when appropriate. Such skills can be developed through experience, observation, and education using a framework that can include mentoring, coaching, and feedback. This review provides some guidance in how to improve leadership skills in OMFS, which we hope will to improve the quality of training and care of patients.